Evaluation of Violence Cases Applying to A Newly Established Forensic Medicine Polyclinic - Özdemir, Miraç (The Bulletin of Legal Medicine, 2024)
Objective: This study examines cases of violence victims who applied to the newly established Forensic Medicine Polyclinic in the first nine months. It aims to discuss the sociodemographic, medical, and judicial characteristics and explore what experts can do to prevent violence, a serious public health issue, and establish justice more effectively. Methods: The forensic reports of violence victims who sought treatment at the Forensic Medicine unit, where the study was conducted, between September 22, 2022, the day of its establishment, and June 22, 2023, as outpatients under law enforcement supervision, were retrospectively examined. Statistical analysis was conducted by evaluating the type of violence, age, gender, application time, findings, consultations, and outcomes. Results: Out of 172 victims, 58.7% were male, 41.3% were female, and 89% were aged 18-65. 63% were brought for examination by law enforcement, with physical violence detected in 97.6%. Sixty-four percent of cases were examined within the first 3 hours, 74.4% had treatable wounds, and women were often attacked at home by their spouses and lovers. Men faced violence from acquaintances in open spaces and workplaces, with cases frequently referred to the psychiatric clinic. Conclusion: Factors such as demographic characteristics (e.g., gender, age), type and duration of violence, and hospitalization are very important in assessing violent incidents. This data helps prevent violence and provide appropriate support and treatment to victims. Collaboration with forensic medicine experts and other branches is useful in forensic case management, especially in emergency departments.